PENGARUH PENDIDIKAN KESEHATAN MEDIA VIDEO ANIMASI TERHADAP PENGETAHUAN CUCI TANGAN PAKAI SABUN PADA ANAK USIA SEKOLAH - dewi pujiana; Selika Prahayu; Puji Setya Rini (Masker Medika, 2024)
ABSTRACT Introduction: Handwashing with soap is one of the sanitary measures by cleaning hands and fingers using water and soap. Washing hands using soap is an effort to prevent disease. In increasing knowledge of washing hands with soap by using animated video media. Objective: To determine the effect of health education animation video media on the knowledge of handwashing with soap in school-age children at SD Negeri X Palembang. Method: This research is a quantitative research with the method "One group pre-test & post-test". The sample in this study was 40 respondents with the Total Sampling technique, the instruments in this study used questionnaires, analysis used statistical tests and Shapiro-wilk tests. This study was conducted on April 29, 2024. Result: The results of the statistical test show the mean value of knowledge before 10.07 and after 13.07 with a p-value of 0.001. Conclusion: There is an influence of health education animation video media on the knowledge of handwashing with soap in school-age children at SD Negeri X Palembang. Keywords : Knowledge, Health Education, Washing Hands with Soap, Animation Videos, School Age Children